2015
DOI: 10.1371/journal.pone.0142643
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Molecular Identity of the W3 Locus and Its Implication in Determination of Flower Colors in Soybean

Abstract: The wide range of flower colors in soybean is controlled by six independent loci (W1, W2, W3, W4, Wm, and Wp). Among these loci, mutations in the W3 locus under the w4 allelic background (i.e., w3w4) produce near-white flowers, while the W3w4 genotype produces purple throat flowers. Although a gene encoding dihydroflavonol 4-reductase, DFR1, has been known to be closely associated with the W3 locus, its molecular identity has not yet been characterized. In the present study, we aimed to determine whether DFR1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…In our previous study, we reported that a 311‐bp indel in the 5′‐upstream region of G . max DFR1 distinguished W3 from w3 (Park et al, 2015). In brief, the w3 allele had the indel and was associated with the disruption of DFR1 expression, whereas the W3 allele did not and was accompanied by a high level of DFR1 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we reported that a 311‐bp indel in the 5′‐upstream region of G . max DFR1 distinguished W3 from w3 (Park et al, 2015). In brief, the w3 allele had the indel and was associated with the disruption of DFR1 expression, whereas the W3 allele did not and was accompanied by a high level of DFR1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…W1 , W2 , Wm , and Wp encode flavonoid 3′5′‐hydroxylase (F3′5′H), myeloblastosis (MYB) transcription factor, flavonol synthase, and flavanone 3‐hydroxylase, respectively (Takahashi et al, 2007, 2013; Zabala and Vodkin, 2005, 2007). W3 and W4 encode dihydroflavonol 4‐reductase (DFR) (Fasoula et al, 1995; Park et al, 2015; Xu et al, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The F 2 population segregated into 86 plants with purple flowers and 24 plants with deep purple flowers. gene) in Chr 17, and DFR3 in Chr 2 (Xu and Palmer, 2005;Yang et al, 2010;Park et al, 2015). All of the 10 F 3 families derived from F 2 plants with deep purple flowers were fixed for deep purple flowers (Table 2).…”
Section: Inheritance and Linkagementioning
confidence: 99%